Postharvest coatings of ‘apple’ banana fruits (Research, Society and Development, 2021)
Banana is a fruit of great importance for Brazilian agribusiness, in terms of consumption by the Brazilian population, second only to orange. Correct handling after harvesting is decisive to favor the longevity of the fruits during marketing, reducing losses caused by mechanical damage and poor packaging. The objective of this work was to evaluate the influence of seven post-harvest coatings on apple banana fruits. The experiment was carried out in a phytotechnic laboratory, using a completely randomized design with five replications. Each parcel consisted of a bouquet with three units of fruit. The treatments evaluated were: T1 = 28% sucupira extract solution; T2 = 57% sucupira extract solution; T3: 14% moringa extract solution; T4 = 9% grape oil solution, T5 = 14% coconut oil solution, T6 = 14% soy oil solution, T7 = 14% wax solution and T8 = Control (no coating applied). Beeswax provided the smallest losses in length, fruit diameter, and loss of fresh fruit mass during the storage period. The sucupira and moringa extracts provided the highest levels of soluble solids at the end of storage, and all coatings used in the post-harvest treatment of bananas reduced the ripening of the fruit.